High toughness and excellent electrical performance bismaleimide resin modified by hyperbranched unsaturated polyester of flexible aliphatic side chains. (August 2021) - Shi, Jiahao; Zhang, Xiaorui; Weng, Ling; Sun, Xue; Zhu, Pingwei; Wang, Qingye
Because of its flawed toughness, the scope of application of bismaleimide resin (BMI) in the field of aeronautics, industry and electricity is greatly restricted. Herein, a novel Hyperbranched unsaturated polymers (HBP) with the flexible chains grafted was incorporated to reinforce BMI resin's toughness, where the new interpenetrating networks (IPN) structure was formed. The rich unsaturated double bond of HBP polyester could react with the BMI resin for chemical crosslinking and be used for the toughening agent. 13 C-NMR and FT-IR were used to characterize HBP's hyperbranched structure. Consequently, after adding 20 wt.% HBP, the impact strength of BMI modified by HBP increased by 211.1%. In comparison with neat BMI, the flexural strength of BMI modified by HBP was enhanced by 209.3%. It is worth noticing that HBP available in BMI resin significantly improved its electrical performance.